PENGARUH PENGGUNAAN SABUK PENGAMAN PADA PENGEMUDI DALAM KASUS TABRAKAN FRONTAL - Berlian Kushari; Pakorn Aniwattakulchai (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2012)
A post-crash two-step analysis was performed on a fatal road accident involving a single-occupant pick-up truck that hit a concrete barrier in an almost perpendicular (frontal) direction. Firstly, the crash event was reconstructed to estimate the value of related parameters, such as collision speed, angle, speed of separation, and collision impulse time. Subsequently, models were developed to study the involved injury mechanismemphasizing on simulating the effects of using seatbelt to the occupant’s body during the collision. Accident reconstruction was carried out using VistaFX3 package software, while MADYMO package software was used in the study of injury mechanism. The results show that the acceleration rate suffered by occupant’shead and thorax (chest) could have been significantly reduced if the seatbelt were used properly.Keywords: traffic accident, safety belt, vehicle speed.